Promosi Kain Batik melalui Media Sosial dengan Pendekatan Tren Berkain - Pramestika, Sintya Ariyanti; Setiawan, Bayu; Ismoyo Aji, Restu (IAI Nasional Laa Roiba Bogor, 2026)
Indonesian traditional cloth or Wastra is a cultural heritage that has aesthetic, philosophical value, and represents the nation's identity that has been passed down by generation. However, along with the development of the times, the interest of the younger generation, especially the current generation of teenagers, towards traditional fabrics tends to decline due to the dominant trend of modern clothing which is considered more suitable for today's lifestyle. This condition has the potential to hinder efforts to preserve traditional fabrics in the future. The high level of internet and social media users among teenagers opens up new opportunities to reintroduce traditional fabrics through a more contextual and interesting approach. This research aims to examine the role of social media as a media for promoting traditional fabrics through promotion with an approach to fabric trends as a form of adaptation of local culture into modern dress styles. The research method used is a descriptive qualitative approach with analysis of social media trends, adolescent audience characteristics, and visual communication elements in digital content. The research results are expected to provide an understanding of the effectiveness of social media with a trend approach to attract the interest of teenagers in traditional fabrics.